PENGARUH PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS DI KABUPATEN PEMALANG) - Arifiah, Nuni; Yuningrum, Heny; Farida, Dessy Noor (Universitas Wahid Hasyim, 2024)
This research aims to analyze the influence of tax understanding and taxpayer awareness on individual taxpayer compliance. The research was conducted in Pemalang Regency. It is hoped that this research will be able to provide information, references, and input for the Directorate General of Taxes in order to increase taxpayer compliance. This research uses primary data. The population in this research is individual taxpayers in Pemalang Regency. The sampling technique used purposive sampling, which was then based on the criteria and calculations of the Slovin formula to determine 100 individual taxpayers. Observations, interviews, and questionnaires were used to collect data in this research. Data analysis was carried out using multiple linear regression tests, which were processed using the SPSS 25 program. The results of this research indicate that understanding taxation partially has a positive effect on individual taxpayer compliance, taxpayer awareness partially has a positive effect on individual taxpayer compliance.Keywords, Taxpayer Awareness, Taxpayer Compliance, Taxation Understanding